The Effect of Annealing on the Structural, Electrical and Optical Properties of CdTe Thin Films - Al-Ali, Ahmed S Ahmed; Ali, Iftikhar M; Al-Haddad, Raad M S (Al-Nahrain Journal of Science, 2016)
CdTe Thin films were deposited by thermal evaporation on glass substrates under vacuum of 2×10-6mbar. The annealing has been done under vacuum 10-3mbar at (303,373,423,473) K annealing temperature. The structure was investigated by XRD technique. It is found that the structure for all samples (as-deposited and annealed) is polycrystalline. The d.c. electrical conductivity was investigated and attributed to two mechanisms. The activation energy Ea increases from 0.13 to 0.55eV as annealing temperature increases from 303 to 473K. The a.c. conductivity reveals that the dependence of activation energy Ew on frequency is larger than that on temperature. Ew increases from 0.11 to 0.18eV as annealing temperature increases from 303 to 473K. Optical studies showed that optical energy gap increases with increasing annealing temperature from 1.4eV at 303K to 2.15eVat 473K.